Induction of Resistance to Larvae Crocidolomia pavonana F. (Lepidoptera: Crambidae) using Rhizobacteria to the Cabbage - Indri Yanil Vajri; Trizelia; Haliatur Rahma (Andalasian International Journal of Entomology, 2024)
Crocidolomia pavonana is a significant pest on cabbage that reduces the quality and quantity of cabbage. Utilizing microorganisms such as rhizobacteria is an alternative environmentally friendly control that can potentially suppress the development of this pest. The study aimed to obtain rhizobacteria isolates capable of colonizing cabbage tissue and inducing plant resistance to C. pavonana larvae. The research was conducted at the Biological Control Laboratory and Greenhouse, Faculty of Agriculture, Universitas Andalas, Padang. The study used a Completely Randomized Design (CRD) with ten treatments and five replications. The treatment consisted of rhizobacteria isolates, including Bacillus thuringiensis, Bacillus subtilis, Serratia marcescens, Stenotrophomonas maltophilia, as well as a negative control (aquadest sterile) and a positive control (Cypermethrin insecticide). The test was carried out by soaking the seeds in a suspension containing rhizobacteria with a population density of 10⁸ cells/ml. The variables observed were larval mortality, pupa and imago formation percentage, and increased salicylic acid production. The data were analyzed using variance and continued with the LSD further test at the 5% level. The results showed that all rhizobacteria isolates colonized into cabbage plant tissue could kill C. pavonana larvae and inhibit these insects' biological development. B. thuringiensis KJKB7.3 showed better results with the highest mortality value (62.67%). Soaking cabbage seeds with rhizobacteria can increase the content of salicylic acid. Based on this research, the rhizobacteria used in the research have the potential to be developed as biological agents to control C. pavonana.